The panoramic dental radiograph for emergency physicians. Issue 9 (26th July 2019) - Sklavos, Anton; Beteramia, Daniel; Delpachitra, Seth Navinda; Kumar, Ricky
Abstract : Dental emergencies are common reasons for presenting to hospital emergency departments. Here, we discuss the panoramic radiograph (orthopantomogram (OPG, OPT) as a diagnostic tool for the assessment of mandibular trauma and odontogenic infections. In this article, we review the radiographic principles of image acquisition, and how to conduct a systematic interpretation of represented maxillofacial anatomy. The aim is to equip the emergency physician with the skills to use the OPG radiograph when available, and to rapidly assess the image to expedite patient management. Included is a discussion of a number of cases seen in the emergency setting and some common errors in diagnosis.